2016
DOI: 10.3389/fpls.2016.00527
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Red Light Night Break Treatment on Growth and Flowering of Tomato Plants

Abstract: Compact and healthy young plants increase crop production and improve vegetable quality. Adverse climatic conditions and shading can cause young plants to become elongated and spindly. We investigated the effects of night break (NB) treatments on tomato plants using red light (RL) with an intensity of 20 μmol·m2·s−1. Tomato plants were subjected to NB treatments with different frequencies ranging from every 1, 2, 3, and 4 h, and plant growth, flowering, and yield were monitored. The results showed that with th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 39 publications
(45 reference statements)
1
16
0
Order By: Relevance
“…Plants sense diurnal variations which affect flowering and accordingly are classified as short- day, long-day and day neutral plants. Importance of darkness in short-day plants is evident from the fact that disruption of dark period with light significantly affects flowering ( Andrés and Coupland, 2012 ; Johansson and Staiger, 2015 ; Cao et al, 2016 ). Under long-day condition, light inhibits the expression of flowering genes; HEADING DATE 3A ( HD3A ) and RICE FT-LIKE1 ( RFT1 ) in rice by activating an inhibitor HEADING DATE 1 (HD1), whereas, under short-days, HD1 induces the expression of HD3A and RFT1 ( Ishikawa et al, 2005 ).…”
Section: Hormonal Regulation Of Plant Development In Darkmentioning
confidence: 99%
“…Plants sense diurnal variations which affect flowering and accordingly are classified as short- day, long-day and day neutral plants. Importance of darkness in short-day plants is evident from the fact that disruption of dark period with light significantly affects flowering ( Andrés and Coupland, 2012 ; Johansson and Staiger, 2015 ; Cao et al, 2016 ). Under long-day condition, light inhibits the expression of flowering genes; HEADING DATE 3A ( HD3A ) and RICE FT-LIKE1 ( RFT1 ) in rice by activating an inhibitor HEADING DATE 1 (HD1), whereas, under short-days, HD1 induces the expression of HD3A and RFT1 ( Ishikawa et al, 2005 ).…”
Section: Hormonal Regulation Of Plant Development In Darkmentioning
confidence: 99%
“…Light intensity and CO 2 are the two most important factors affecting the photosynthetic process being, respectively, its energy source and carbon substrate (Muneer et al , Tomimatsu et al ). Healthy and robust plants are essential if we are to maximise fruit yield and quality (Cao et al ), so these plant qualities are necessary if we are to meet the food demands of our increasing human population (Toor et al ). To optimise the CO 2 and light environment for tomatoes, a better understanding of the effects of CO 2 and light intensity on tomato leaf gas exchange and growth is critical.…”
Section: Introductionmentioning
confidence: 99%
“…Shinners) were increased by all the supplemental light conditions than in the control. The enhancement of seedling quality is not only duo to supplemental lighting but also duo to night interruption.Similarly, Cao et al [24] reported that night break not only increased stemdiameter, leaf number, and fruit fresh weight, but also resulted in more compact and healthier plant of tomato. Yoneda et al [25] also found night interruption treatments (4 h) combined with 8 h photoperiod increased leaf biomass of tomato to amounts observed under LD conditions.…”
Section: Growth Development and Morphologymentioning
confidence: 89%
“…More importantly, a study reported that supplemental lighting during nighttime is more effective to promote plant growth and yield as compared with daytime both in summer and winter [23]. Furthermore, night-interruption not only increase leaf biomass and crop yield but also result in more compact and healthier plants [24][25][26]. In commercial production, supplemental light intensity is usually between 100 and 200 µmol·m −2 ·s −1 photosynthetic photon flux density (PPFD) [27,28].…”
mentioning
confidence: 99%